Humanization of an anti-mucin antibody for breast and ovarian cancer therapy. - Baker, T; Bose, C; Caskey-Finney, H; King, D; Lawson, A; Lyons, A; Mountain, A; Owens, R; Rolfe, MR; Sehdev, M (1994)
Antibody-drug conjugates utilize the targetting potential of antibodies to improve the potential of cytostatic or cytocidal drugs. One such murine monoclonal antibody, CTM01 (mCTM01), which recognizes an epitope on breast epithelial mucin, has potential for the treatment of breast and ovarian cancers. We examine in this paper the comparative properties of mCTM01 against a number of other anti-mucin antibodies. We then describe the humanization and high level re-expression of humanized CTM01 (hCTM01), a process designed to avoid the immune response to administered murine antibodies in human patients and to produce sufficient material for clinical studies. We show that the humanized form has properties superior to mCTM01 in terms of binding affinity to antigen presented on tumour cells.